Impact evaluation using Difference-in-Differences. Issue 4 (30th September 2019) - Fredriksson, Anders; Oliveira, Gustavo Magalhães de
Abstract : Purpose: This paper aims to present the Difference-in-Differences (DiD) method in an accessible language to a broad research audience from a variety of management-related fields. Design/methodology/approach: The paper describes the DiD method, starting with an intuitive explanation, goes through the main assumptions and the regression specification and covers the use of several robustness methods. Recurrent examples from the literature are used to illustrate the different concepts. Findings: By providing an overview of the method, the authors cover the main issues involved when conducting DiD studies, including the fundamentals as well as some recent developments. Originality/value: The paper can hopefully be of value to a broad range of management scholars interested in applying impact evaluation methods.